Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Dalam Menurunkan Kesulitan Keuangan Perusahaan - Nabil Zuhdi; Helisa Noviarty; Rusliyawati Rusliyawati (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2024)
This research analyzes the influence of profitability, leverage, company size in reducing financial difficulties. The research method uses quantitative research. The research samples are companies in the oil, gas and coal sectors listed on the Indonesia Stock Exchange (BEI) from 2020 to 2023. Sample selection was done by observing company data on the IDX regarding profitability, leverage and company size. Data analysis uses the Smart PLS application with a multiple linear regression approach. The research results show that profitability in a company positively influences the level of financial difficulty. Meanwhile, leverage has a negative impact on the level of economic distress. This research also indicates that market response can strengthen the influence of profitability and leverage in a company on the level of financial distress, but not significantly. The implications of this research have strengthened agency theory regarding information imbalance between management and investors in the context of supervision and transparency. Thus, this research recommends the importance of management strengthening stricter monitoring mechanisms and transparency to reduce information imbalances, enabling investors to make more appropriate decisions based on a more accurate assessment of the company's financial condition. The novelty of this research is the presence of market response as a moderating variable.